A five-year library development plan for U.P. College Tacloban - Patacsil, Perla C. (1981)
This study is a plan for the University of the Philippines College Tacloban library for the academic years 1981-82 to 1985-86. The main objective is to provide the college with a blueprint that would give the library the needed direction for its full development. The ultimate goal is to develop a well-organized and effective library services program for the present and potential library users through the provision of a relevant, up-to-date, and well-balanced collection, qualified and competent library personnel, adequate facilities, and a dynamic library administration.